The Impact of Democratic Concepts on the Advanced Interpretation of the Constitutional Document - Dakheel , Munir Hmood (Thi Qar Arts Journal, 2022)
The texts of the Constitution do not elaborate its provisions in a precise detail that encompasses all its parts. Otherwise, monitoring their details in the texts of the Constitution requires anticipating them from the beginning, and eventually leads to these texts slipping into mistakes that should have been avoided, and to be erased sometimes in what they contradict, which contradicts what the constitutions envisage. In most cases, from a brief that surrounds the wide range of issues that regulate them, and a summary that does not delve into their details, in order to remain steadfast through the flexibility of their application across many generations whose interests and needs vary, in light of the steady development in democratic values that dominate the world. And there is no sin that the constitutional oversight body, in its developed interpretation of the constitutional document, does not extract the values that give preference to when deciding on constitutional issues, but rather considers them and makes them more likely because its society requires them, even if it sometimes deduces them from the comparative organization, if its prevalence among civilized nations is indicative of their vitality and humanity